Analysis of Decisions to Use Airport Self-Check-In Service Products - Candra Ananda; Muhammad Syahril; Juliater Simarmata (Dinasti International Journal of Digital Business Management, 2024)
This article is a scientific literature review that focuses on the decision analysis of using airport self-check-in service items. It falls within the field of marketing management science. The objective of this article is to formulate a hypothesis concerning the correlation between various aspects, with the intention of subsequently utilizing it as a foundation for further investigations within the realm of human resource management. The research employed a descriptive qualitative research methodology. The data utilized in this study is derived from prior research that remains pertinent to the present inquiry. Information was gathered from prominent scholarly online platforms, such as Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The results obtained from this study are presented below: 1) The decision to utilize airport self check-in service products is influenced by product socialization. 2) The decision to utilize airport self check-in service products is influenced by the behavior of service users. 3) The decision to utilize airport self check-in service products is influenced by the effectiveness of technology usage.